Corrosion Inhibition and Adsorption Process of 3-Amino-5-Mercapto-1,2,4-Triazole on Aluminium Alloy: Experimental and Theoretical Studies - Guo, Xin; Wang, Jinke; Huang, Luyao; Wang, Yajie; Ma, Li; Zhang, Dawei; Ma, Lingwei (Frontiers in Materials, 2022)
The corrosion inhibition effect of 3-amino-5-mercapto-1,2,4-triazole (AMT) on AA2024 aluminium alloy in 3.5 wt.% NaCl solution was investigated, and the corrosion inhibition mechanism was revealed. The influence of AMT concentration on the corrosion inhibition performance was evaluated by potentiodynamic polarization curve and electrochemical impedance spectroscopy (EIS). Surface analysis and surface-enhanced Raman scattering (SERS) spectra were used to study the adsorption process and corrosion inhibition mechanism of AMT on the alloy surface. Polarization curve and EIS results showed that when the AMT concentration was 1.5 g/L, the corrosion current density (icorr) was the lowest and the resistance of adsorption film (Rf) was the largest, illustrating the highest corrosion inhibition efficiency. Moreover, the adsorption kinetics process of AMT was revealed by SERS measurement, and a positive correlation between the SERS intensity and Rf values of AMT after different immersion time was achieved. It indicated that the efficient adsorption of corrosion inhibitors significantly enhanced the corrosion inhibition performance. Density functional theory (DFT) and molecular dynamics simulations were used to give further insight into the adsorption and inhibition mechanism of AMT on the aluminium alloy surface.